One Health and planetary health research landscapes in the Arab world - Shaher Zyoud; Sa'ed H. Zyoud (Science in One Health)
This review explored research trends in One Health and planetary health in the Arab world, a region confronting major sustainability challenges. These fields are crucial in combating global pressing concerns like infectious diseases, biodiversity loss, antimicrobial resistance, climate change, and air pollution. The COVID-19 pandemic stressed their significance to global health and sustainable development. This analysis assessed the Arab world's contributions to these concepts applying performance analysis and visualization mapping, revealing that One Health outperformed planetary health in terms of productivity and number of contributed countries. Egypt, Saudi Arabia, and the United Arab Emirates have emerged as leading contributors to One Health and planetary health research in the Arab world. Meanwhile, the United States and the United Kingdom, as non-Arab nations, play a pivotal role in fostering collaborative efforts with the region. The trajectory of One Health research has indeed shown remarkable exponential growth, especially since the beginning of the COVID-19 pandemic in 2019, which is an indication of increasing relevance in the address of global health challenges. Conversely, planetary health presents an irregular growth pattern, with a strong point in the development of this area standing out in 2023. The unique set of social, cultural, governance, and agricultural attributes of the Arab region are joined by major environmental challenges that define the focus of both One Health and planetary health research efforts. Climate change, environmental contexts, and public health feature prominently in both One Health and planetary health, with One Health focusing mainly on infectious diseases and planetary health addressing the implications of climate change on human health. Advancing these concepts demands the establishment of a regional governing body to oversee an integrated One Health and planetary health strategy, foster regional research communities and alliances, secure political will and funding, and ensure the integration of these concepts into policy and academic frameworks.